Stress superposition characteristics and roof structure control of recovery room in close distance coal seam - Zizhao FU; Jianbiao BAI; Shuai YAN; Dong ZHANG; Xiaodong ZHENG; Guangjun SUN; Yongjie WANG (Meitan kexue jishu)
The stress disturbance and complex roof situation of the pre excavation recovery room of the close range coal seam group result in severe damage to the surrounding rock of the tunnel during the construction of the recovery room, making it difficult to control the surrounding rock. Taking the 1205 working face recovery room of a certain mine as the background, a mechanical model of the roof of the close range coal seam group recovery room is constructed, the depth of the upper coal seam working face floor failure is estimated, the evolution law of the roof rock fractures of the lower coal seam recovery room is simulated and inverted, the instability mechanism of this type of tunnel is revealed, and a comprehensive stability control technology for surrounding rock is proposed and verified on site engineering. The results show that: By establishing a mechanical model of the roof of the recovery room during the final mining period, it is determined that under the geological conditions of the mine, the support resistance P1≥3.05 MPa in the recovery room can ensure the stability of the surrounding rock of the recovery room after the working face and recovery room are connected; Using empirical formulas optimized by multiple linear and nonlinear regression analysis, it is estimated that the depth of failure of the upper coal seam working face floor is greater than 8.41 m and less than the interlayer spacing of 13.3 m; Using the UDEC numerical calculation model, the evolution law of cracks on the roof of the recovery room was inverted, and reinforcement measures were taken 10 m in advance for the roof of the recovery room under the goaf, and 15 m in advance for the roof of the recovery room under the coal pillar; Propose a comprehensive stability control technology for the combined active and passive support of anchor cables and individual pillars in the recovery room, as well as the advanced pre cracking of the surrounding rock in the inner roof of the coal pillar lower channel, and apply it to different stress affected areas of the recovery room. The monitoring results of mine pressure indicate that during the construction of the recovery room of the working face, the deformation of the surrounding rock is small, the force changes of the anchor rods and cables are small, and the control effect of the surrounding rock is good, ensuring the safe and efficient retreat of the 1205 working face.